The discovery of a new Iron Age ritual complex in central Oman: recent excavations near Ādam - Gernez, Guillaume; Jean, Mathilde; Benoist, Anne (Proceedings of the Seminar for Arabian Studies, 2017)
Recent excavations near Ādam (Oman) yielded new data about the margins of the desert in central Oman during the early and late Iron Age periods. After nine campaigns of excavations and surveys in the area around Ādam, only a few graves had been identified during the surveys and the excavations of two graveyards (Ādam north and south) but settlement sites were scarce and it seemed that the area was not highly occupied during this period, unlike the situation observed at the major site of Salūt, only 45 km north-west of Ādam. The discovery of an enigmatic Iron Age site near Ādam, however, leads us to reconsider this first impression. The site consists of a group of structures located on the eastern tip of Jabal MiΡmār (MuΡmār, Mudhmar, MaΡmār), near Wādī Дalfayn. The main stone building contains unique copper weapons (actual size, reduced models, and miniatures) including arrows, bows, quivers, and daggers that could have been used for a ritual purpose. One other building was excavated, and the micro-regional topography and survey provided further data on the function of the site. From its geographic location and its unusual content, the site could have several functions: a meeting place linked to social, political, or religious use, and a staging post on the ancient road between Ādam and Sinaw.